Therapeutic hypothermia and N-PASS; results from implementation in a level 3 NICU. (October 2019) - Üner, Inger Louise; Johansen, Tove; Dahle, Julie; Persson, Mette; Stiris, Tom; Andresen, Jannicke Hanne
Abstract: Background: Neonates that have been subjected to perinatal asphyxia and fulfill criteria for therapeutic hypothermia are cooled to 33.5 °C for 72 h. There is no consensus regarding sedation and analgesic use during hypothermia, but there is evidence supporting the importance of pain relief and adequate sedation. There is a need for assessment of the neonates need for pain relief and sedation, and for adjustments of medication to ensure adequate treatment. There are many different scoring tools available. We found the N-PASS (Neonatal Pain, Agitation and Sedation Scale) scoring tool to be the most suitable for this patient group as it assesses both pain and sedation. Methods: We translated the scoring tool according to guidelines published by Wilder et al., and scored neonates treated with therapeutic hypothermia. Sedation and analgesia were adjusted according to scoring results. At the end of the study a questionnaire was filled out by the nurses in charge of this group of patients. Results: Both pain and sedation scores did not reach the desired levels until day 3. The nurses reported a high level of satisfaction (79.7% were extremely of very satisfied), and 96.7% of the nurses found the neonates to be better pain relieved after the initiation of the study. Conclusion: The implementation of the N-PASS scoring tool in our unit has been successful, and has led to better pain relief and sedation than before the implementation. Highlights: Neonates undergoing therapeutic hypothermia need adequate sedation and pain relief. N-PASS scores both pain and sedation. Implementing N-PASS scoring in the assessment of neonates undergoing therapeutic hypothermia led to better pain management. The nurses were very satisfied with the scoring tool.